Loop‐Mediated Isothermal Amplification (LAMP) for the Diagnosis of Sexually Transmitted Infections: A Review - Yasaman Ahmadi; Yejiong Yu; Zhanfeng Cui; Wei E. Huang; Monique I. Andersson (Microbial Biotechnology)
ABSTRACT Sexually transmitted infections (STIs) remain a significant public health concern. Given the asymptomatic nature of many STIs, diagnostic testing is critical for determining the appropriate treatment, enabling effective tracing and reducing the risk of further transmission. Nucleic acid amplification tests (NAATs) are the most sensitive and the most widely used in well‐resourced settings. The majority of available NAATs are based on polymerase chain reaction (PCR), which requires highly trained personnel and costly equipment, making it impractical for resource‐limited settings. Loop‐mediated isothermal amplification (LAMP) has emerged as a simple, rapid, sensitive and low‐cost alternative for pathogen detection, particularly well‐suited for point‐of‐care tests (POCT). In this review, we evaluate LAMP assays reported in the literature for the detection of pathogens linked to the high incidence STIs prioritised by the World Health Organization (WHO) for POCT in 2023. These include Neisseria gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis, T. pallidum subspecies pallidum, as well as other common STIs such as herpes simplex virus, hepatitis B virus and human immunodeficiency virus (HIV). For each LAMP assay, we identified and summarised the key elements such as the type and number of tested clinical specimens, chosen target gene, detection system, reference test and clinical outcomes. We highlight the advantages and limitations of these assays and discuss the gaps that should be addressed to improve their applicability for POCT.